VD_FINDINFO Faillite / 2011 / 77 vom 20. Januar 2012 - VD Tribunal cantonal (2012)
ACTE DE RECOURS, CONDITION DE RECEVABILITÉ, DÉLAI DE RECOURS, MOTIF DU RECOURS | 149 CPC (CH), 321 al. 1 CPC (CH), 321 al. 2 CPC (CH)